Culture is a moderator of the interaction between financial inclusion and financial performance - Yogantara, Komang Krishna; Yadnyana, I Ketut; Sudana, I Putu; Sujana, I Ketut (Mercados y Negocios, 2025)
This study examines how the integration of local culture can enhance the connection between financial inclusion and the financial success of MSMEs in Bali. A survey was conducted on Hindu export-oriented MSME owners in Bali. Questionnaires, document analysis, and interviews were used to collect data, which were then analyzed using the SEM-PLS technique. The research findings show that, although financial services do not have a statistically significant effect, other results indicate a beneficial effect on financial performance. Additionally, local culture was found to strengthen this relationship. The study supports the Resource-Based Theory as a theoretical contribution, making it relevant in reducing barriers to the growth of MSMEs. The relevance of this article lies in providing new insights from the perspective of users, namely MSMEs, whose numbers are still relatively small, particularly in terms of utilising unique local genius values to enhance the interaction between financial inclusion and MSMEs’ financial performance.